EXPRESSION OF ANIMAL SYMBOLS IN ENGLISH AND UZBEK PROVERBS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
the article highlights the expression of symbols in English and Uzbek folk Proverbs, which are considered folk oral creations. In some places, the semantics of Proverbs related to animal names in English and Uzbek are analyzed